2013
DOI: 10.3109/07420528.2012.754451
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Circadian Clocks—A Conserved Phenotype?

Abstract: The circadian system of mammals regulates the timing of occurrence of behavioral and physiological events, thereby optimizing adaptation to their surroundings. This system is composed of a single master pacemaker located in the suprachiasmatic nucleus (SCN) and a population of peripheral clocks. The SCN integrates time information from exogenous sources and, in turn, synchronizes the downstream peripheral clocks. It is assumed that under normal conditions, the circadian phenotype of different peripheral clocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
(106 reference statements)
1
9
0
Order By: Relevance
“…Interestingly, in a previous study using the same rats, we found that the peak expression of Per2, Bmal1 and Dbp are synchronized across the olfactory bulb, liver and tail skin [8]. Furthermore, the rhythms of expression of each of these genes peaks in close temporal proximity with the rhythm in the DG (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Interestingly, in a previous study using the same rats, we found that the peak expression of Per2, Bmal1 and Dbp are synchronized across the olfactory bulb, liver and tail skin [8]. Furthermore, the rhythms of expression of each of these genes peaks in close temporal proximity with the rhythm in the DG (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Data for olfactory bulb, liver and skin are based on previously published results [8] using the same rats used in the present study for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities have been observed both during episodes of illness and remission (Etain et al, 2011). There were even suggestions to use peripheral circadian clock as conserved phenotype for genetic analyses (Weigl et al, 2013). PER3 gene is known for its associations with sleep patterns.…”
mentioning
confidence: 99%
“…Daily cycle is observed in hormone production, cell regeneration or brain waves activity (Schibler et al, 2003). Organism adapt to its surroundings when circadian clock works appropriate (Ramanathan et al, 2012;Weigl et al, 2013).…”
mentioning
confidence: 99%